IMPROVEMENT TO STUDENTS’ ACHIEVEMENT IN PROCEDURAL TEXT COMPOSITION THROUGH PROCESS APPROACH-BASED MIND MAPPING EMPLOYMENT - As-shidiqi, Asâ€™ad Rizki; ., Flora; Sukirlan, Muhammad (Inspiratif Pendidikan, 2022)
The purpose of this study was to investigate whether there is a significant improvement in students’ writing achievement after being taught using Process Approach-Based Mind Mapping, as well as which aspect of students’ writing enhances the most. A quantitative study using a pre-experimental design was carried out which involved 15 ninth-grade students of SMPN 38 Bandar Lampung. The instruments used in this research were writing tests whichwere analyzed using Paired Sample T-test through SPSS 16.0. The results demonstrated that students’ writing achievement significantly improved from pretest to posttest after being taught using Process Approach-Based Mind Mapping and the most enhancement aspect of writing was content. Process Approach-Based Mind Mapping could be utilized to assist students organize their thoughts by allowing for individual brainstorming using graphics and providing students with a structured writing direction. Process Approach emphasizes four key stages: planning, drafting, editing (reflecting and revising), and final version.